Expression of Progestrone Receptor and Proliferative Marker ki 67, in Various Grades of Meningioma - Nasrin Shayanfar (Acta Medica Iranica, 2010)
Meningiomas are slow-growing neoplasms which recur locally, their morphologic grading is simple but do not always correlate with patient outcome. The aim of present study is to evaluate the status of progesterone receptor (PR) and proliferation marker Ki67 in various grades of meningioma in a group of Iranian patients. 78 cases of meningioma were selected from the file of a hospital university. All archival H&E stained sections were reviewed and regraded according to WHO criteria. Immunohistochemical analysis for PR and Ki67 was performed on formalin- fixed, paraffin- embedded samples. PR status considered positive if > 10% of tumor cell’s nuclei were strongly immunoreactive, or if > 50% of nuclei were stained with medium intensity. The Ki67 labeling index (LI) is defined as the percentage area with strongest immunostaining. PR were positive in 61/63(96.8%) of grade I tumors,2/10(20%) of grade II,and 0/5(0%) of grade III tumors.Ki67 LI was %2.98±2.27 in grade I tumors, %9.30±5.79 in grade II tumors and %34.00±5.47 in grade III tumors. For both markers, differences between grade I,II and III tumors were significant(P<0.001).There was a reverse relationship between mean of Ki67 LI and PR status,with increasing grade of tumor. Evaluation of PR status and Ki67 LI together with conventional histologic evaluation can help in providing more information about the biologic behaviour of meningiomas,especially for those that histological grading is not straightforward.